Strategi Pendidikan Dalam Perspektif Al Qur’an dan Pemikir Muslim - Nurrohmah, Cika Auliya; Sodiq, Akmad (PT. Riset Press International, 2026)
Educational strategies play a very important role in achieving educational goals, because learning success is not only determined by the quality of the material, but also by the accuracy of the approach and strategies used. Communicative and contextual delivery is more easily accepted by students compared to monotonous delivery. From an Islamic perspective, educational strategies refer to the Quran and Hadith as the primary sources that serve as the normative foundation, which were then developed by Muslim thinkers in the form of educational theories and practices. This research aims to examine and analyze the concept of educational strategies according to the Quran and the views of Muslim thinkers. This research uses the library research method by examining various tafsir, hadith, and works by Muslim thinkers. The research findings indicate that Islamic education strategies include expository strategies (Surah An-Nahl: 125), interactive strategies (Surah Al-Baqarah: 31), empirical strategies (Surah Al-Ghasyiyah: 17–20), and inquiry strategies (Surah Al-‘Ankabut: 20). In conclusion, educational strategies from the perspective of the Quran and Muslim thinkers are holistic and integrative, and are oriented toward the formation of the perfect human being. The implications of this research are expected to serve as a reference in the development of more effective and valuable Islamic education practices.